2022
DOI: 10.1007/s10644-022-09392-6
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between fiscal imbalances, green fiscal spending, and green economic growth: empirical findings from E-7 economies

Abstract: The green economy is viewed as a cost-effective means of achieving sustainability around the globe, and a recent study inferred the nexus between the fiscal imbalances and green economic growth based on E-7 economies data. This paper attempts to answer how green fiscal spending ensures green economic growth and stabilizes fiscal imbalances in E-7 economies. The study findings highlighted the mechanism and viability of green fiscal spending for fiscal imbalances and green economic growth. More specifically, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…One such macroeconomic imbalance is the inability to achieve satisfactory growth rates. The government seeks to achieve satisfactory growth rates by boosting public and private investments (Fang and Chang 2022). Issuing EU common debt is a tool aimed at achieving satisfactory growth rates, especially during periods of imbalances, such as the pandemic crisis, but also the energy crisis due to armed conflicts.…”
Section: Market Failuresmentioning
confidence: 99%
“…One such macroeconomic imbalance is the inability to achieve satisfactory growth rates. The government seeks to achieve satisfactory growth rates by boosting public and private investments (Fang and Chang 2022). Issuing EU common debt is a tool aimed at achieving satisfactory growth rates, especially during periods of imbalances, such as the pandemic crisis, but also the energy crisis due to armed conflicts.…”
Section: Market Failuresmentioning
confidence: 99%
“…Wang and Yu found that environmental tax rates have a positive impact on pollution reduction and green innovation [31]. Concerning green fiscal expenditures, Fang and Chang conducted an empirical study based on data from E-7 economies and concluded that green fiscal expenditure is beneficial to green economic development [32]. Hussain et al demonstrated that green government subsidies significantly decrease CEs and promote green development [33].…”
Section: The Impact Of Green Public Financementioning
confidence: 99%
“…China’s manufacturing industry urgently needs to advance the formation of a resource-saving and environmentally friendly industrial structure and manufacturing system through transformation and upgrading to support for green economic growth 5 . As an incentive-based industrial policy that emphasizes an innovation-driven and eco-civilized development path through the development and implementation of an intelligent and green manufacturing system, Made in China 2025 is a significant initiative for promoting the manufacturing industry’s transformation and upgrading, providing solid economic support for green economic growth 6 . To promote the effective implementation of this industrial policy, fully mobilize localities to explore new modes and paths of manufacturing development, and strengthen the urban manufacturing industry’s influential demonstration role in advancing the green transition, the Ministry of Industry and Information Technology of China successively launched 30 Made in China 2025 pilot cities (city clusters) in 2016 and 2017.…”
Section: Introductionmentioning
confidence: 99%